Development of teaching materials writingdescription using graphic organizer forstudent class V elementary school - Rahmi Hidayati; Darnis Arief; Syahniar Syahniar (Fakultas Ilmu Pendidikan UNP)
This research is based on teaching materials that are less suitable with curriculum demands, less adjusting to writing process (pra writing, when writing, and post writing), and less interest of students to write descriptions. This study aims to determine the validity, practicality and effectiveness of teaching materials write description using Three Word Main Idea Map. The type of research is development research. This research uses 4-D model which consists of 4 stages: define, design, develop, and disseminate. Validity test data obtained through the implementation of RPP sheet, assessment of teacher and student responses. The effectiveness is seen from the activity, the assessment of the process and the result of writing the description. Based on the validity, practicality, and effectiveness test obtained the percentage is very valid, very practical, and very effective for every aspect. Based on the assessment of the results of writing description can be seen the percentage of mastery of writing results increased descriptions. Based on these results, it is concluded that teaching materials to write descriptions using Three Word Main Idea Map developed can improve the skills of writing descriptions.